Structural gender discrimination and its systemic understanding in the human rights system - Iriarte Rivas, Claudia Paz (Anuario de Derechos Humanos, 2018)
This article is based on the feminist legal studies concept, which states the need to introduce in the international human rights systematically the idea of structural gender discrimination as a mechanism to approach the material reality of women as subjects and emphasizes the social gender conflict to make a step in overcoming the systemic legal discrimination women are exposed to. In the first place we will analyze the way in which was taken up the abstract notion of the subject configured by the constitutionalism. Then we will analyze how this concept, still present as a substrate of the International Human Rights, has impeded that the ongoing progress in the International Human Rights referred to women gives way to substantial changes. We also analyze how the understanding of the concept of structural discrimination might facilitate the deconstruction of the concept of the initial subject and the construction of a concept which takes into account the subjectivity of diverse subjects and their materiality.